(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Necessary conditions have been created for the economic development of our country and the implementation of new enterprise projects. In particular, there are enough opportunities for the activities of enterprises specializing in yarn and fabric production.